Drafting an effective ethical code of conduct for professional societies: A practical guide - Margaret C. Hardy (Administrative Sciences, 2016)
Academic, medical, and research communities are struggling to quickly and effectively address unethical conduct within their professional ranks. Without a policy in place, individuals and institutes are subject to convoluted procedures and unnecessary consequences. In addition to policies geared to prevent harassment and assault, it is important to protect the ethical basis for research and provide a set of guidelines for how professionals treat each other, students, and trainees. Since drafting a policy of this nature is complex, 10 guidelines are provided as a framework for how to draft, implement, and establish an ethical code of conduct. Further implications for nonprofit societies and professional societies in particular are discussed.
Keywords: 350; accountability; diversity; ethics; governance; inequality; organizational change; research and development